my usual approach is to start with the "messy" side, and change everything to sines and cosines.
LS
=(1- sinx/cosx)/(1 - cosx/sinx)
= (cosx-sinx)/cosx * (sinx)/ (sinx - cosx)
= (-1)sinx/cosx
= -tanx
perform similar steps for the second one, bet you'll get it
solve each identity algebraically
1)(1-tanx)/(1-cotx)=-tanx
2)(1+cotx)/(1+tanx)=cotx
3 answers
I got (1- sinx/cosx)/(1 - cosx/sinx)
but how did (1- sinx/cosx) turn to (cosx-sinx)/cosx?
but how did (1- sinx/cosx) turn to (cosx-sinx)/cosx?
nevermind, found out :) thanks